Cumulative life damage in dermatology - Kristina Ibler; Gregor B.E. Jemec (PAGEPress Publications, 2011)
Cumulative life damage is an old concept of considerable face validity, which has attracted more scientific interest in the fields of sociology and psychology than in medicine over the years. The research examines the interconnectivity of the many factors which shape the development of individuals or institutions over time. By focussing on time, context and process, life course research highlights the different effects seemingly similar events may have at different points in time and in different contexts.